Handbook of nonlinear optics - Richard L Sutherland; McLean, Daniel G; Kirkpatrick, Sean (Boca Raton CRC Press, 2020)
Examining classic theories, experimental methods, and practical formulas for exploration of the core topics in nonlinear optics, the second edition of this acclaimed text was extensively revised to reflect recent advances in the analysis and modification of material properties for application in frequency conversion, optical switching and limiting
Keywords: Propagation, Velocity, Measurement of light